Mutational effects on enhancing the stability of Geobacillus zalihae T1 lipase in non-aqueous organic solvents - Maiangwa, Jonathan Stallon (2017)
Lipases are one of nature`s most endowed group of proteins when considering their broad functional biotechnological and industrial relevance. The fundamental and technological conditions requirements for enzymes hampers the application of lipases as biocatalysts. Central to these challenges are the space and time in prospecting for natural enzymes with biocatalytic properties. In this respect, naturally obtained lipases are engineered and designed into biocatalysts that can efficiently be used. Inspired by the proven thermostability and diminished solvent stability of a lipase from Geobacillus zalihae, this dissertation addresses the impediment of solvent stability by way of directed evolutionary construction of mutant variants capable of maintaining important structural elements, protein folding and stability in high concentrations of organic solvents. Firstly, the behavior of T1 lipase was investigated in hydrophilic chain length organic solvents by molecular dynamic simulations. For this purpose, the dynamics, and the conformational changes folding transitions, stability and structural dynamics which alters interactions between solvent molecules and amino acid residues was investigated. The RMSD revealed the effects, decreasing solvent polarity had on the protein`s simulation dynamics and equilibrium state. Residue motions were influenced greatly in butanol and pentanol water mixtures. Comparatively the residue RMSF and SASA was correspondingly higher to flexibility and vice-versa. More hydrogen bonds in methanol, ethanol, and propanol water mixtures were formed and thus, it is assumed that correlated increase in intraprotein hydrogen bond is linked to stability of the protein. Solvent accessibility analysis revealed an exposure of hydrophobic residues in all solvent mixtures with polar residues buried away from the solvent. Furthermore, it was observed that the active site pocket was not conserved in organic solvent mixtures. This attribute was proposed to be responsible for the weakened strength in the catalytic H-bond network and most likely a drop in catalytic activity. Altogether, the data obtained suggests that the solvent-induced lid domain conformational opening was gradual. The additional formation of cooperative network of hydrogen bonds and hydrophobic interactions could render stability to the protein in some solvent system. Dynamic cross-correlated atomic motions between the atoms from atomic coordinates was in concerted functional network with regions of residues of the lid domain. Geobacillus zalihae T1 lipase was used as a parent lipase for random mutagenesis and mutant variants with stability in polar organic solvents were constructed. The solvent stability of the mutant variants in a broad range of 50, 60 and 70 % of methanol, ethanol, propanol, butanol, and pentanol at a temperature of 60 oC was retained in six (6) mutants A83D/K251E, R21C, G35D/S195N, K84R/R103C/M121I/T272M, R106H/G327S. Mutant A83/K251E acquired enhanced organic solvent stability with higher stability in methanol as compared to other mutants. The models of these mutants as well as each mutation residue built in silico and analyzed for their conformational stability, showed significant stable conformational fold of mutants. Structural analysis of various networks of covalent interactions of the mutant models was found to reveal further formation of hydrogen bonds and hydrophobic networks which stimulated folding and stability. Site-directed mutagenesis constructs of beneficial single mutants G35D, A83D, M121I, S195N, K251E, T272M and G327S was further resolved. Significantly, butanol and pentanol diminished stability of mutants whereas about 60 % of residual stability was maintained particularly for methanol in mutants M121I, S195N and T272M. Furthermore, stable single mutants assembled in a combinative approach via sitedirected mutagenesis, yielded mutants A83D/M121I/K251E/G327S and A83D/M121I/S195N/T272M with improved stability towards 50, 60, and 70 % methanol, ethanol, and propanol. Kinetic investigation showed higher km and Vmax ranging from 0.003529 μM and 588 μmoles/min/mL respectively, for best mutants. The half-life was significantly higher for all mutant proteins in methanol, although the mutants had better exponential decay constant. Visible circular dichroism (CD) on the possible changes of the secondary structure of selected improved mutants in 50 % and 60 % methanol, showed overall, thermally-induced unfolding of mutants accompanied with some loss of secondary structure content at relative methanol solvent conditions. Perturbations on the protein matrix, including a significant net loss of secondary structure triggered a secondary structure reorganization that led to an increase or decrease in the structural elements content. The spectral differences in 50 % methanol suggests a considerable peak shifts in all mutant proteins as compared to that in buffer. The secondary structure formation of the α-helix, β-sheets, β-turns and random coil were preserved among all mutant proteins with observed changes in the β-turn. This illustrates how changes in the structural organization are intertwined with conformational interplay of the protein backbone in organic solvents. The relative contribution of various structural interactions in respect to the overall protein stability of the best mutants via molecular dynamics simulations revealed the interplay between structural features and the conformational stability of the protein. Changes in residue motions leads to the proposition that the higher stability in some mutants may not appear to be directly correlated to the hydrophobicity of residues. Protonation of some residues also affected both the stability and the conformational dynamics of the protein fold. Evidence of gain in both hydrogen bonds and hydrophobic interactions indiscriminately contributed to overall stability. Observations derived from MD simulations, suggests that hydrophilic polar organic solvents play important role in the dynamical conformational diversity of proteins. Short distances of radial distribution function provided the required distance of interaction between atoms which enables hydrogen bond formation and hydrophobic interactions for stability. The solvent stability and secondary structural characteristics of mutants A83D/M121I/S195N/T272M and A83D/M121I/K251E/G375S indicates robust and improved variants that can act as biocatalyst for industrial applications. Newly formed structural interactions between mutant residues and other surrounding residues will enhance the native conformation flexibility in non-aqueous reaction media and hence promoting stability.